If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (1200 + -60x)(20 + 2x) = 0 Multiply (1200 + -60x) * (20 + 2x) (1200(20 + 2x) + -60x * (20 + 2x)) = 0 ((20 * 1200 + 2x * 1200) + -60x * (20 + 2x)) = 0 ((24000 + 2400x) + -60x * (20 + 2x)) = 0 (24000 + 2400x + (20 * -60x + 2x * -60x)) = 0 (24000 + 2400x + (-1200x + -120x2)) = 0 Combine like terms: 2400x + -1200x = 1200x (24000 + 1200x + -120x2) = 0 Solving 24000 + 1200x + -120x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '120'. 120(200 + 10x + -1x2) = 0 Factor a trinomial. 120((20 + -1x)(10 + x)) = 0 Ignore the factor 120.Subproblem 1
Set the factor '(20 + -1x)' equal to zero and attempt to solve: Simplifying 20 + -1x = 0 Solving 20 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -1x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -1x = 0 + -20 -1x = 0 + -20 Combine like terms: 0 + -20 = -20 -1x = -20 Divide each side by '-1'. x = 20 Simplifying x = 20Subproblem 2
Set the factor '(10 + x)' equal to zero and attempt to solve: Simplifying 10 + x = 0 Solving 10 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + x = 0 + -10 x = 0 + -10 Combine like terms: 0 + -10 = -10 x = -10 Simplifying x = -10Solution
x = {20, -10}
| y=18x+5 | | -2-10n=68 | | 4(7-6x)=-20 | | 21+23=35+16 | | Log[4](33.3)= | | w+6= | | -4(-2+a)=52 | | x/(x-3)=8 | | 12x/(-4x) | | -5(m-5)=-60 | | a+-3+3=-2 | | 2.9(-5-1)-4.4(-5-7)= | | 175m-75m+58500=60300-200m | | x(3+3)=64.5 | | 7(2h-4)+3h=108 | | x(2+2)=64.5 | | 2.5x+0.5x=5+3.5x | | 360-(13x)=114 | | x(2+2)=43 | | x+2+2=43 | | 3/4×36 | | (8+3x+5x^2+8x^3)+(5-3x+5x^2-8x^3)= | | 12x-34=85-5x | | 4x=2y-4-20 | | 7(5x-2)=6(6x-1)x | | 16=7x-33 | | -1+5y=-16 | | 5r^2-44r+120=-30+111r | | -9+6b=9+3b | | 36+(24)3= | | -15=6+7y | | 4x+5+5x+22=90 |